Halal Tourism at Dama Batang Park, Kabupaten Padang Pariaman: Analysis of Sharia Guidelines Implementation of DSN-MUI No. 108/DSN-MUI/X/2016 - Oktapia, Annisa' Suryani; Wira, Ahmad; Rozalinda, Rozalinda; Fernanda, Ahmad (Likuid Jurnal Ekonomi Industri Halal, 2025)
This paper is to examine the appropriateness of implementing halal tourism in the Dama Batang Park tourist attraction in accordance with the standardized criteria outlined in DSN MUI fatwa No. 16 of 2016. This research methodology employs qualitative techniques, utilizing field research and exploratory analysis for data processing. The study utilizes both primary and secondary data sources. Primary data sources are derived directly from observational interviews with management of the Dama Batang Park tourist attraction, while secondary sources are extracted from DSN-MUI Fatwa No. 16 of 2016, books, and publications published in the Open Journal System (OJS) concerning halal tourism. The data analysis technique applied involves a series of steps, including classification, exposing data, verifying the data obtained through the analysis of standardization values with the results of field findings, and producing conclusions from the data that has been collected and presented. The results of these findings explain that several standardization values have been written in the fatwa so that it becomes a reference in assessing whether the tourist attraction is halal or not. Then after being analyzed, in general, the Dama Batang Park tourist attraction has met the criteria as a halal tourist attraction, but several shortcomings can be resolved immediately such as the community selling merchandise that does not have a halal certificate and the use of e-money in transactions, the community still uses conventional financial institutions.